Structural Comparison Between MHC Classes I and II; in Evolution, a Class-II-Like Molecule Probably Came First - Yanan Wu; Nianzhi Zhang; Keiichiro Hashimoto; Chun Xia; Johannes M. Dijkstra (Frontiers in Immunology, 2021)
Structures of peptide-loaded major histocompatibility complex class I (pMHC-I) and class II (pMHC-II) complexes are similar. However, whereas pMHC-II complexes include similar-sized IIα and IIβ chains, pMHC-I complexes include a heavy chain (HC) and a single domain molecule β2-microglobulin (β2-m). Recently, we elucidated several pMHC-I and pMHC-II structures of primitive vertebrate species. In the present study, a comprehensive comparison of pMHC-I and pMHC-II structures helps to understand pMHC structural evolution and supports the earlier proposed—though debated—direction of MHC evolution from class II-type to class I. Extant pMHC-II structures share major functional characteristics with a deduced MHC-II-type homodimer ancestor. Evolutionary establishment of pMHC-I presumably involved important new functions such as (i) increased peptide selectivity by binding the peptides in a closed groove (ii), structural amplification of peptide ligand sequence differences by binding in a non-relaxed fashion, and (iii) increased peptide selectivity by syngeneic heterotrimer complex formation between peptide, HC, and β2-m. These new functions were associated with structures that since their establishment in early pMHC-I have been very well conserved, including a shifted and reorganized P1 pocket (aka A pocket), and insertion of a β2-m hydrophobic knob into the peptide binding domain β-sheet floor. A comparison between divergent species indicates better sequence conservation of peptide binding domains among MHC-I than among MHC-II, agreeing with more demanding interactions within pMHC-I complexes. In lungfishes, genes encoding fusions of all MHC-IIα and MHC-IIβ extracellular domains were identified, and although these lungfish genes presumably derived from classical MHC-II, they provide an alternative mechanistic hypothesis for how evolution from class II-type to class I may have occurred.